EFFECT OF MNEMONIC STRATEGIES ON VOCABULARY MASTERY AND READING LITERACY: A META-ANALYSIS - Muhammad Syahril; Merry Lapasau; Widodo (University of Kuningan, 2026)
Literacy is a fundamental educational element that extends beyond decoding written symbols to include understanding, using, and reflecting on information, with vocabulary mastery playing a critical role in supporting reading comprehension and overall academic success. This meta-analysis aims to quantitatively synthesize existing research on the effectiveness of mnemonic strategies in enhancing vocabulary acquisition and reading literacy, while also exploring moderating factors that influence these outcomes to provide evidence-based guidance for educational practice. This study employed a rigorous quantitative meta-analytic design using a random-effects model to synthesize effect sizes from 35 empirical studies across various educational levels, examining the direct and mediated effects of mnemonic strategies on vocabulary mastery and reading literacy, while ensuring reliability through a systematic review process, transforming diverse statistical data into standardized effect sizes, addressing heterogeneity and publication bias, and exploring moderator variables through sensitivity and subgroup analyses to provide comprehensive and generalizable insights into the effectiveness of mnemonic instruction. The meta-analysis revealed a significant pooled effect size of 0.81 (95% CI: 0.79 to 0.84) for mnemonic strategies on vocabulary mastery and reading literacy, alongside a significant heterogeneity (Q(34) = 49.47, p = 0.042), indicating variability in effectiveness across studies likely influenced by moderating factors such as learner characteristics and instructional context. Despite this variability, the relatively low heterogeneity (τ = 0.04) and robust model fit (AIC and BIC values) suggest that mnemonic strategies generally produce strong and consistent positive effects on literacy outcomes across diverse educational settings.